'A sort of black and white past and present thing': high school students' subject positions on South Africa's recent past. Issue 6 (1st November 2016) - Ferreira, Ana
Abstract: This article examines the discursive positions South African high school students take up in response to a teaching intervention that invites them to historicize their identities. It thus seeks to contribute to the growing body of education research on how to meaningfully engage young people in post-conflict societies with their recent past. Drawing on lesson transcripts as well as post-intervention focus group discussions with students in two different high schools, I use poststructuralist theories of discourse and subjectivity to attempt to understand students' reluctance to see themselves as historically located. The analysis shows that students feel interpellated in uncomfortable ways by a historical narrative that works to tie subject positions to fixed, racialized identities. Their attempts to escape these predetermined positions constitute ongoing negotiation of multiple discourses tied to race, history and their generational locations. Implications for curriculum and pedagogy are briefly considered.